THE MODULATION OF RAT LIVER MICROSOMAL CALCIUM ION-PUMPING ATPase BY DICOPHANE AND LOW PROTEIN INTAKE (1992)
The effects of the liver tumour promoter, dicophane, with those of low protein intake (LPI) on the functional expression of rat liver microsomal Ca(2+) -ATPase were compared. The effects of dicophane and LPI on the activity of the microsomal enzyme after carcinogenic initiation by pretreatment with aflatoxin B (AFB), a genotoxic liver carcinogen, were also compared. The Status of membrane - bound Ca(2+) -ATPase of erythrocytes of humans having primary liver cancer (PLC) and kwashiorkor was assessed. The specific activity of membrane - bound microsomal Ca(2+) -AT Pase of the livers of untreated rats was 4.543 ± 0.857 µmole P/mg protein/hr. at pH 8.0 and was insensitive to calmodulin. The specific activity of the enzyme was significantly decreased (P < 0.01) following subcutaneous administration of a single dose of 75mg dicophane/kg body wt.; the affinity of the enzyme for Ca(2+) was however unaffected. Similarly, liver microsomal Ca (2+)-ATPase activity was significantly diminished following the ingestion of low protein diet by rats for 12 weeks. The mean Ca(2+) -ATPase activity of AFB -treated animals (in the absence of dicophane) was not significantly different (P > 0.05) from that of AFB-treated rats which subsequently received dicophane. In contrast, liver microsomal Ca(2+)-ATPase activity of animals fed low protein diet prior to and after AFB ingestion was higher (P < 0.05) than that of animals which were on low protein diet only. Basal activity of erythrocyte Ca(2+) -ATPase in paediatric controls and those having kwashiorkor (protein-energy-malnutrition) were similar (P > 0.05); similar observations were made between normal adults and those suffering from PLC. Erythrocyte Ca(2+) -ATPase of either PLC or kwashiorkor patients was however, some- what, less sensitive (15-40 %) to the stimulatory effect of calmodulin, an endogenous activator of the Ca(2+) -pump. These results suggest that liver microsomal Ca(2+) -ATPase could be a useful biochemical marker to determine the onset or occurrence of tumour promotion in liver cells. Finally, chronic dietary protein malnutrition mimics the effect of chemical liver tumour promoters and could possibly enhance the development of human PLC particularly n those areas of the tropics where malnutrition is prevalent. Future confirmatory experiments are however re-quired to fully justify this postulate.